Humus forms, earthworm bioturbation and soil organic carbon storage in Chernozems of the low-intensity land use of steppe zone of Ukraine - Yakovenko, Volodymyr; Gorban, Vadym; Kotovych, Oleksandr; Didur, Oleh; Poleva, Julia (Geoderma Regional, 2025)
Chernozems of the low-intensity land use systems of the steppe zone of Ukraine are an important factor of sustainable development, contributing to the conservation of natural resources and maintaining a balance between agricultural productivity and environmental protection. The aim of the study was to assess the humus state of Chernozems of the low-intensity land use systems of the steppe zone of Ukraine under the influence of different types of vegetation (Wildland, Shelterbelts and Native forest). The humus state was determined by such characteristics as humus forms, intensity of earthworm bioturbation, content and reserves of soil organic carbon (SOC), SOC/clay ratio. Humus forms were classified according to Keys of classification of humus systems and forms. The content of earthworm casts was calculated in thin sections as a percentage of the total number of aggregates of the 2–0.25 mm fraction of the surface layer. Soil organic carbon was determined by the titration method, with subsequent calculation of its reserves in the soil layer. The SOC/clay Ratio was used to determine the soil structure qualities class and the level of soil layer saturation with humus. The comparison of quantitative characteristics of soils under the influence of different types of vegetation was carried out by statistical methods (descriptive statistics, ANOVA/MANOVA, multiple comparison of means according to the Tukey criterion). It was found that humipedons of Wildland Chernozems belong to the Mesomull humus form, humipedons under Shelterbelts and Native forest belong to Oligomull. Earthworm casts content in Native forest Chernozem is 3.5 and 2.9 times higher than in Chernozems under wildland steppe vegetation and artificial forest, respectively. SOC/clay Ratio for Native forest statistically significantly (p ˂ 0.05) exceeds the indicators for Wildland and Shelterbelts. The dependence of the distribution of SOC reserves in the thickness of the studied soils on the type of vegetation was established, according to which the SOC reserve for Native forest statistically significantly (p ˂ 0.05) exceeds this indicator for Wildland and Shelterbelts by 1.42 and 1.40 times, respectively. Thus, the type of vegetation significantly affects the quantity, quality of humus and the overall humus state of Chernozems of the steppe zone of Ukraine under low-intensity land use. The results of the study will be useful for diagnosing organic matter transformations, accounting for carbon reserves in soils of steppe landscapes of Ukraine, and monitoring the humus state of Chernozems that are actively used in agriculture.